Effect of diet composition on acid–base balance in adolescents, young adults and elderly at rest and during exercise - Hietavala, E-M; Stout, J R; Hulmi, J J; Suominen, H; Pitkänen, H; Puurtinen, R; Selänne, H; Kainulainen, H; Mero, A A (European journal of clinical nutrition, 2015)
Background: Diets rich in animal protein and cereal grains and deficient in vegetables and fruits may cause low-grade metabolic acidosis, which may impact exercise and health. We hypothesized that (1) a normal-protein diet with high amount of vegetables and fruits (HV) induces more alkaline acid–base balance compared with a high-protein diet with no vegetables and fruits (HP) and (2) diet composition has a greater impact on acid–base balance in the elderly (ELD). Subjects/methods: In all, 12–15 (adolescents (ADO)), 25–35 (young adults (YAD)) and 60–75 (ELD)-year-old male and female subjects ( n =88) followed a 7-day HV and a 7-day HP in a randomized order and at the end performed incremental cycle ergometer tests. We investigated the effect of diet composition and age on capillary (c-pH) and urine pH (u-pH), strong ion difference (SID), partial pressure of carbon dioxide ( p CO 2 ) and total concentration of weak acids ( A tot ). Linear regression analysis was used to examine the contribution of SID, p CO 2 and A tot to c-pH. Results: In YAD and ELD, c-pH ( P ⩽0.038) and u-pH ( P <0.001) were higher at rest after HV compared with HP. During cycling, c-pH was higher ( P ⩽0.034) after HV compared with HP at submaximal workloads in YAD and at 75% of V O 2 max (maximal oxygen consumption) in ELD. The contribution of SID, p CO 2 and A tot to c-pH varied widely. Gender effects or changes in acid–base balance of ADO were not detected. Conclusions: A high intake of vegetables and fruits increases blood and u-pH in YAD and ELD. ELD compared with younger persons may be more sensitive for the diet-induced acid–base changes.